Molecular epidemiology and clonality of Acinetobacter spp in a Lebanese hospital over a period of one year - Micheline Soudeiha; Elie Salem Sokhn; Ziad Daoud; Dolla Sarkis (Journal of Infection in Developing Countries)
Introduction: The worldwide emergence of antimicrobial resistance in Acinetobacter spp and their clonal dissemination call for the investigation into Acinetobacter spp epidemiology.